(untitled) (Research, Society and Development, 2021)
This article addresses the understanding of the use of scientific language and its relevance in Mobility Engineering publications, which demonstrates the researcher’s skills by structuring their areas of knowledge, such as persuasion strategies and subjectivity aspects. Furthermore, it discusses the use of citations and incidence in academic and scientific texts. This study aimed to identify the most recurrent types of citations (direct or indirect) in the main national publications on Mobility Engineering available on the Capes Periodical Portal. For this purpose, the bibliometric technique was used for data collection in order to analyze all articles published from 2001 to 2020, highlighting the types of citations. A total of 179 scientific articles was analyzed. As for the results of the analysis, they showed that the articles were marked by relevant differences in terms of the number of citations. From the survey of citations in the analyzed published articles, it was observed that the authors used a significant number of indirect citations, about 81.91%, demonstrating mastery of the chosen themes and applying them through scientific language in a clear and understandable way.